Collagen Biomarkers Indicate Increased Tissue Damage in Connective Tissue Disorders: Biomarker Kolagen Mengindikasikan Peningkatan Kerusakan Jaringan pada Gangguan Jaringan Ikat - Ahmed Nassir Faisal (Academia Open, 2025)
Background: Connective tissue disorders such as rheumatoid arthritis, osteoarthritis, and systemic lupus erythematosus are characterized by chronic inflammation and collagen degradation, which contribute to tissue damage and disease progression. Specific Background: Collagen degradation biomarkers, including matrix metalloproteinases (MMP-1, MMP-9), tissue inhibitors of metalloproteinases (TIMP-1), and inflammatory markers (CRP, TNF-α), reflect the extent of tissue remodeling and inflammation. However, limited studies comprehensively evaluate their diagnostic and prognostic value in these disorders. Knowledge Gap: There is insufficient evidence comparing the levels of these biomarkers between patients with connective tissue disorders and healthy individuals, particularly regarding their role in disease monitoring and progression. Aims: This study aims to assess and compare collagen degradation biomarkers (MMP-1, MMP-9, TIMP-1, CTX, CRP, TNF-α) between patients with connective tissue disorders and healthy controls to explore their diagnostic and prognostic significance. Results: Patients exhibited significantly elevated levels of MMP-1, MMP-9, TIMP-1, CTX, CRP, and TNF-α compared to healthy controls (p < 0.05), suggesting increased collagen turnover and chronic inflammation. BMI was also significantly higher in patients (p = 0.003). Novelty: This study provides comprehensive comparative data on multiple biomarkers, highlighting the simultaneous elevation of collagen degradation and inflammatory markers as potential indicators for disease severity. Implications: These findings suggest that assessing collagen degradation biomarkers can enhance early diagnosis, monitor disease progression, and guide therapeutic strategies for connective tissue disorders. Highlights: Collagen biomarkers indicate tissue damage in connective tissue disorders. Compare collagen biomarkers in patients and healthy controls for diagnostic value. Biomarkers are significantly elevated in patients, indicating increased collagen turnover and inflammation. Keyword: Collagen degradation, MMPs (Matrix metalloproteinases), TIMP-1 (Tissue inhibitor of metalloproteinases), CTX (C-terminal telopeptide of collagen), Chronic inflammation, Connective tissue disorders